The Effect of The Use of Artificial Intelligence Technology on The Digital Literacy Skills of Grade VI Students of SDI Surya Buana - Afgani, Muh. Noaf; Rohmah, Azida Nur; Asy'ari, Muhammad Ma'ruf; Mardhiyah, Ainatul (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
This study aims to analyze the impact of using Artificial Intelligence (AI) technology on the digital literacy skills of 6th-grade elementary school students. Digital literacy encompasses the ability to search for, evaluate, and effectively use information from digital platforms. The research method used is the correlational method. The research sample consisted of 48 students randomly selected from the 6th grade of an elementary school. The results showed that students who used AI technology in the learning process experienced a significant improvement in their digital literacy skills. This study concludes that the application of AI technology in the learning process can enhance students’ digital literacy and recommends integrating AI into the elementary school curriculum to optimize students’ potential in facing the challenges of the digital era.